2021
DOI: 10.1007/s11060-021-03761-3
|View full text |Cite
|
Sign up to set email alerts
|

The growth rate and clinical outcomes of radiation induced meningioma undergoing treatment or active monitoring

Abstract: Introduction Radiation induced meningioma (RIM) incidence is increasing in line with improved childhood cancer survival. No optimal management strategy consensus exists. This study aimed to delineate meningioma growth rates from tumor discovery and correlate with clinical outcomes. Methods Retrospective study of patients with a RIM, managed at a specialist tertiary neuroscience center (2007–2019). Tumor volume was measured from diagnosis and at subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
12
1
1
Order By: Relevance
“…These ndings are consistent with Gillespie et al, whose institutional retrospective study of similar design reported a recurrence rate of 50% and a median progression time of 28 months [12], compared to our cohort with a 73% recurrence rate, and mean progression of 81.4 months. Broadly, the utility of radiation for the treatment of RIMs has not been well characterized.…”
Section: Discussionsupporting
confidence: 93%
“…These ndings are consistent with Gillespie et al, whose institutional retrospective study of similar design reported a recurrence rate of 50% and a median progression time of 28 months [12], compared to our cohort with a 73% recurrence rate, and mean progression of 81.4 months. Broadly, the utility of radiation for the treatment of RIMs has not been well characterized.…”
Section: Discussionsupporting
confidence: 93%
“…2 and 3 and a summary of observed correlations and prognostic factors of tumor growth is presented in Table 2. These ndings are in sharp contrast to a recent study by Gillespie and Islim, where a mean growth rate of 0.62 cm³ per year and RGR of 72% per year were described for RIM [14]. Notably, the mean baseline volume of 4.9 cm³ found in their study was also signi cantly higher (almost 25 times) when compared to ours.…”
Section: Rim Volume and Growth Characteristicscontrasting
confidence: 99%
“…Furthermore, the growth rate of RIMs has not been widely studied [14], particularly using volumetric methods. Volumetric analysis of RIMs growth patterns would be meaningful for both the patient and oncologist since patients treated in their childhood with RT for cancer are undergoing regular brain imaging with small, asymptomatic meningiomas being frequently diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Patient sex, age, presenting clinical features, the WHO performance status, and Age-Adjusted Charlson Comorbidity Index (ACCI) were included [ 16 , 20 ]. The risk factors associated with meningioma development, including a history of cranio-spinal radiation, hormone replacement therapy, and genetic syndromes were recorded [ 3 , 21 , 22 ]. The radiological features of the meningioma before the first operation were recorded.…”
Section: Methodsmentioning
confidence: 99%